Usytuowanie fonologicznych cech dystynktywnych w strukturze poszczególnych typów cech głosowych - Lapis, Włodzimierz (Investigationes Linguisticae, 2008)
Based on the analysis of entries from Polański 1999, the present work – as its title indicates - explores “the location of phonological distinctive features in the structure of individual types of voice features”. The exploration of this topic will enable us to properly comprehend the notion of ‘distinctiveness’ (primarily in linguistics, but - through natural expansion - also in other domains of sciences). We will address such questions as: what it is (and what it is not), how to understand it, what kinds of distinctiveness exist, and which of its aspects we might deal with.